Detection of Salmonella In Some Red and White Frozen Meat Obtained From Local Market. - Mohammed, Sudad J. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Salmonella spp. are one of the most frequently reported causes of bacterial foodborne outbreak in the world.Objective: This study has been conducted to detect salmonella as a major public health problem worldwide.Methods: A total of 12 samples including 8 white meat (chicken) and 4 red meat (beef) samples were collected randomly from each sample; 25gr was separated and treated with 225ml of buffered peptone water, incubated at 37C°and 42C° for 24 hours. Samples were streaked on selective enteric agar.Result: Totally 4 out of 8 chicken meat and one out of 4 red meat samples were contaminated with Salmonella spp.Conclusion: These results confirmed the previous findings stating the proper packaging of meat products can effectively decrease the rate of microbial contamination.